Comparative Study of Antitumor Active Cyclo(Gly-Leu) Dipeptide: A Computational and Molecular Modeling Study - Çelik, Sefa; Özel, Ayşen E.; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2016)
The conformational behavior and vibrational spectra of cyclo(Gly-Leu) dipeptide, which is an important biological active compound and a therapeudic agent, have been investigated by computational methods. The theoretically possible stable conformers of free cyclo(Gly-Leu) dipeptide in electronic ground state were obtained by performing conformational analysis following DFT calculations. Further, to predict the intermolecular hydrogen bonding interactions in solid phase, various dimer structures were modeled. The optimized geometry and the wavenumbers for cyclo(Gly-Leu) and its dimers have been calculated by DFT method with B3LYP functional, 6-31++G(d,p) basis set. The complete assignment of the bands was performed based on the potential energy distributions (PED%) and experimental wavenumber shifts upon N-deuteration. General agreements between the observed and calculated frequencies are shown. Chemical interpretation of hyperconjugative interactions was carried out by natural bond orbital (NBO) analysis. Finally, HOMO and LUMO energy levels have been calculated. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Cyclic Dipeptides; DFT Calculations; Glycine; Leucine; NBO Analysis; Vibrational Analysis; Density-Functional Theory; Ab Initio; Vibrational Analysis; Crystal Structure; Dft Calculations; Solid State; L-Leucine; Super-Sensitivity; Aqueous-Solution; Raman-Spectra